Learning through mistakes in crisis management as a strategy of low losses in conditions of continuous uncertainty - T. V. Mokeeva (Вестник университета)
The article examines the problem of crisis management in conditions of continuous uncertainty. It is considered how leaders and the organisations they lead can maintain reputation, financial and operational strength, and competitive advantage in a crisis. The basics of understanding the essence of the crisis, its main factors and origins, are analysed. Leaders are judged on how they deal with the organisation’s most difficult challenges. The article presents the concepts of anti-crisis management, the principles of effective anti-crisis response. The typical mistakes are identified and the possibility of learning through mistakes is explored to reduce losses in a crisis situation.The article will be useful for heads of organisations for making management decisions.